AMERICAN PRINCIPLE ‘KISS’ IN CREATING ENGLISH-LANGUAGE MULTIMEDIA CONTENT - Kharchenk , O. (Collection of scientific papers «ΛΌГOΣ», 2022)
The study focuses its attention on the pragmatic and effective methodology of the English language teaching to students whose majors are publishing, journalism, and editing, who are aimed at creating their own informational, fiction, and nonfiction content. The conducted research reveals a number of key steps of the English language teaching, which combine the specific methodology of teaching, psycholinguistic moments, and consulting the material relating to a number of stylistic figures and literary devices, used actively in American and British communicative spaces. The application of this methodology is proved by more than 1,000 works written in English by Ukrainian students in the form of opinion articles, book reviews, listicles, essays, blogs, and short stories for English multimedia outlets.